Evaluation of Maternal and Perinatal Outcomes in Pregnancy with Preeclampsia at Aljala Maternity Hospital - Laylay Ammar; Amel Morgham; Nasreen Osman; Marwa Rajab (AlQalam Journal of Medical and Applied Sciences, 2024)
Hypertensive disorders of pregnancy (HDP) accounts for 18% of maternal deaths worldwide, with an estimated number of about 62, 000–77, 000 deaths occur each year. The current study aimed to assess maternal and perinatal outcomes of pregnancies complicated by hypertension in Aljala Maternity Hospital. A retrospective, descriptive, case series analysis for four hundred patients was done on the outcome of hypertensive disorder among pregnant women who admitted and were managed at Aljala teaching hospital with preeclampsia during the years 2019 and 2020. Demographic data involving age, parity, gestational week, clinical and laboratory findings were recorded from the medical files. Additionally, delivery route, indications of cesarean section, fetal and maternal complications were determined. The current finding reported high prevalence of perinatal and maternal mortality among pregnant women with preeclampsia. Moreover, other severe maternal and perinatal complications such as Hemolysis Elevated Liver Enzyme Platelet (HELLP) syndrome, placental abruption, eclamptic fits, as well as low birth weight were also commonly reported. The current study showed early onset of preeclampsia was associated with increased risk of developing adverse maternal-fetal/neonatal outcomes compared to late-onset after 36 weeks. Our findings call for special consideration and close surveillance of those women with early-onset diseases. تمثل اضطرابات الحمل الناجمة عن ارتفاع ضغط الدم 18% من وفيات الأمهات في جميع أنحاء العالم، ويقدر عدد الوفيات التي تحدث كل عام بحوالي 62,000-77,000 حالة وفاة. تهدف الدراسة الحالية إلى تقييم النتائج الأمومية والفترة المحيطة بالولادة لحالات الحمل المعقدة بسبب ارتفاع ضغط الدم في مستشفى الجلاء للولادة. تم إجراء تحليل وصفي بأثر رجعي لسلسلة حالات لأربعمائة مريضة حول نتائج اضطراب ارتفاع ضغط الدم بين النساء الحوامل اللاتي أدخلن إلى مستشفى الجلاء التعليمي وخضعن للعلاج في مستشفى الجلاء التعليمي مصابات بتسمم الحمل خلال عامي 2019 و2020. البيانات الديموغرافية التي تتضمن العمر والولادات وأسبوع الحمل وتم تسجيل النتائج السريرية والمخبرية من الملفات الطبية. بالإضافة إلى ذلك، تم تحديد مسار الولادة، ومؤشرات العملية القيصرية، ومضاعفات الجنين والأم. أفادت النتيجة الحالية عن ارتفاع معدل وفيات الفترة المحيطة بالولادة ووفيات الأمهات بين النساء الحوامل المصابات بتسمم الحمل. علاوة على ذلك، تم أيضًا الإبلاغ بشكل شائع عن مضاعفات خطيرة أخرى للأمهات والفترة المحيطة بالولادة مثل متلازمة انحلال الدم المرتفع في إنزيم الكبد، وانفصال المشيمة، ونوبات الارتعاج، فضلاً عن انخفاض الوزن عند الولادة. أظهرت الدراسة الحالية أن البداية المبكرة لتسمم الحمل كانت مرتبطة بزيادة خطر الإصابة بنتائج سلبية على الأم والجنين/المواليد مقارنة بالبداية المتأخرة بعد 36 أسبوعًا. تدعو النتائج التي توصلنا إليها إلى إيلاء اهتمام خاص ومراقبة وثيقة لهؤلاء النساء المصابات بأمراض مبكرة